ESTABLISHMENT AND DEVELOPMENT OF RUSSIAN REVIVAL STYLE IN RUSSIAN EMPIRE ARCHITECTURE IN 19TH CENTURY - Tatiana Sergeevna Semichevskaya (RUDN Journal of Russian History, 2015)
The article shows the process of the establishment and development of the so-called “Russian style” in the Russian Empire’s architecture in the 19th century, which in foreign historiography is also known as the Russian revival style. The article demonstrates the importance of choosing a perfect state policy in architecture to match with the growing mood of national honor after the glorious victory in the Patriotic War of 1812, the style that will show all the beauty and greatness of our country. The author examines the changes the style takes and the symbolic meanings that the Russian revival architecture holds within to become an object of commemoration of the national tradition, to depict the history in stone and to save it for ages. Nowadays the interest in the Russian revival style architecture is constantly increasing. It can be observed in the lately constructed churches in the “Russian-byzantine” style, in the scientific researches of this style in architecture and international conferences held in this sphere.